REVERSE PHASE aHIGH PERFORMANCE LIQUID CHROMATOGRAPHY AND ULTRA VIOLET SPECTROPHOTOMETRIC METHOD FOR THE ESTIMATION OF RALTEGRAVIR POTASSIUM IN BULK (Global Journal of Medical Research, 2011)
A High Performance Liquid Chromatographic (method A) and Ultra Violet spectrophotometric (method B) method were developed and validated for quantitative determination of Raltegravir potassium. The different analytical performance parameters such as linearity, precision, accuracy, limit of detection (LOD), limit of Quantification (LOQ) were determined according to International Conference on Harmonization (ICH) Q2B guidelines. Reverse phase High Performance Liquid Chromatography (method A) and Ultra Violet (method B) were developed for the determination of Raltegravir potassium in bulk and pharmaceutical dosage forms. The chromatographic separation was achieved on Symmetry C18 (4.6 x 150mm, 5 μm XTerra) column using a mixture of phosphate buffer (pH 3.0): Methanol (45:55% v/v) as the mobile phase at a flow rate 0.6 mL min-1. The Ultra Violet spectrophotometric determination was performed at 219 nm. The Linearity of the calibration curves for the analyte in the desired concentration range is good (r2 = 0.999) by both High Performance Liquid Chromatography (method A) and Ultra Violet (method B) spectroscopic method. Both methods (A&B) were accurate and precise with recoveries in the range of 98-100 % and percentage relative standard deviation (RSD less than 2%). The proposed methods were highly sensitive, accurate, and precise and hence was successfully applied for the reliable quantification of Active Pharmaceutical Ingredient content in the commercial formulation.
Keywords: Raltegravir potassium; RP-HPLC; UV Spectrophotometry; Validation; Pharmaceutical product and Quantitation